1996
DOI: 10.1042/bj3140781
|View full text |Cite
|
Sign up to set email alerts
|

Fibrates induce mdr2 gene expression and biliary phospholipid secretion in the mouse

Abstract: Disruption of the murine mdr2 gene leads to the complete absence of biliary phospholipids. We tested the hypothesis that the increase in biliary phospholipid output induced by fibrates is mediated via induction of the hepatic mdr2 gene and its encoded product, the P-glycoprotein canalicular flippase. Increased levels of mdr2 mRNA were observed in the liver of mice treated with different fibrates : ciprofibrate, 660p155 % (as compared with control group) ; clofibrate, 611p77 % ; bezafibrate, 410p47 % ; fenofibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
110
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 45 publications
8
110
2
Order By: Relevance
“…Fibrates including bezafibrate have been reported to up-regulate expression of multiple resistant gene 2 (mdr2) in the mouse (Chianale et al, 1996). They have demonstrated that an increase of mdr2 expression by fibrates secreted hepatic phospholipid into the biliary tract and inactivated hydrophobic endogenous bile acids in the biliary tract by micellization (Chianale et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrates including bezafibrate have been reported to up-regulate expression of multiple resistant gene 2 (mdr2) in the mouse (Chianale et al, 1996). They have demonstrated that an increase of mdr2 expression by fibrates secreted hepatic phospholipid into the biliary tract and inactivated hydrophobic endogenous bile acids in the biliary tract by micellization (Chianale et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrates including bezafibrate have been reported to up-regulate expression of multiple resistant gene 2 (mdr2) in the mouse (Chianale et al, 1996). They have demonstrated that an increase of mdr2 expression by fibrates secreted hepatic phospholipid into the biliary tract and inactivated hydrophobic endogenous bile acids in the biliary tract by micellization (Chianale et al, 1996). Moreover, mdr2-knockout mice revealed that the initial pathologic lesion was chronic nonsupportive destructive cholangitis similar to the one in primary biliary cirrhosis (Smit et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…10 Alternatively, the administration of fibrates, statins, or peroxisome proliferators, which all have been shown to induce biliary phospholipid secretion by the induction of Mdr2, making bile less toxic, might pose a therapeutic approach to prevent bile duct complications after OLT . [35][36][37] However, these compounds may induce other hepatic injury and have considerable side effects. 38 In conclusion, our data indicate that toxic bile composition, because of a high biliary bile salt/phospholipid ratio, acts synergistically to ischemia/reperfusion injury in the origin of bile duct injury after OLT.…”
Section: Discussionmentioning
confidence: 99%
“…Mediated by PPAR-alpha (peroxisome proliferator activated receptor alpha), fibrates can also induce abcb4 in mice 14,15 . Human PPAR-alpha activation patterns differ from mice, so that benzfibrates do not induce ABCB4 expression in man 16 .…”
Section: Physiology and Regulationmentioning
confidence: 99%
“…• Fibrates are anti-hyperlipidemic agents that up regulate ABCB4 gene transcription via PPAR-alpha, with the potential to increase biliary phospholipids secretion 9,14,17 . Data using benzfibrates in primary biliary cirrhosis suggests that the function of ABCB4 can be augmented to increase PC secretion 37 .…”
Section: Treatmentmentioning
confidence: 99%